Monitoring and Evaluation of the Implementation Process of the State Policy to Promote the Development of Civil Society in Ukraine - Prykhodchenko, Liudmyla L.; Krupnyk, Andrii S.; Orlova, Alla I.; Dulina, Oksana V. (International Journal of Criminology and Sociology, 2021)
Among the components of the cycle of state policy to promote the development of civil society in Ukraine, the process of its implementation is studied. In particular, the current state of monitoring and evaluation (ME) of this process was analysed, scientific developments on this topic were reviewed and the authors' own approach to the implementation of state policy in this area was proposed. The ME of the process of implementation of the National Strategy for Civil Society Development for 2016-2020 in Ukraine (hereinafter – the National Strategy) as the main legal act that ensures the implementation of state policy in this area at national, regional and local levels of public administration, was studied. The basic requirements to the organisation of the ME of the process of implementation of the National Strategy in terms of periodicity, multilevel, organisational and methodological support, forms of control were formulated. A set of evaluation criteria and indicators was proposed and recommendations for the organisation of this process were provided. The provided recommendations can be the basis for the creation and implementation of the ME system for the implementation of the National Strategy. The results of the ME process of implementation of the current National Strategy can be used in the development of a new National Strategy for the next period after 2020.